H is for Hinterland - 10 Erotic Short Stories - Jones, Julie (Saga Egmont, 2023)
'H is for Hinterland - 10 Erotic Short Stories' is a collection of erotica which delves into "the land behind" and all things anal, taking its name from the slang term "hinterland" meaning anal and ass-related.